Comparação de performance entre banco de dados relacional PostgreSQL e NoSQL MongoDB - Martinello, Jhonatan (2021)
Data storage has always been of paramount importance in any project or application, and for this, relational databases are widely used. However, with the popularization of the internet, the increase in the volume of data from social networks, mobile and web applications is increasing, giving strength to the use of NoSQL database by new projects. However, there is still a lot of questioning about how the relational database would perform when working with these large amounts of data. This article aims to compare the performance between PostgreSQL relational database and NoSQL MongoDB, query performance of data usually stored in NoSQL databases, manipulating large amounts of data. Queries were performed on the PostgreSQL relational database and on the NoSQL MongoDB database in order to compare the execution speed, using native resources from both databases to improve their permanence. Tests carried out prove that the PostgreSQL database with the correct use of its resources had better results than MongoDB.